Femtosecond laser additive manufacturing of micro-3D optical devices and their applications - Li, Shufan (Nanyang Technological University, 2021)
Femtosecond laser direct writing (FsLDW) technology is a novel additive manufacturing (AM) method that is newly developed in recent years. AM technology addresses the shortcoming of conventional manufacturing methods in fabricating complex geometric micro-optical structures. Commercial optical lenses are fabricated by subtractive manufacturing, such as grinding and etching, and formative manufacturing, such as moulding. However, they are not suitable for manufacturing micro and nano-sized optical elements. Due to AM’s flexibility in the free-shape fabrication and the high resolution into the micro-/nano-dimension, it has drawn attention in the optical fields. Optical device miniaturization with complex structures and specific applications is actively sought out. There have been developments in micro-fabrications by stereolithography (SLA), digital light processing (DLP), or chemical vapor deposition (CVD) via electron beam lithography (EBL). Still, these methods encounter one or some drawbacks in terms of time and energy-consuming, material option, and resolution. I seek a fast and precise fabrication method that can produce customized optical elements and devices with miniature thickness and dimension. The femtosecond (fs) laser machining and fabrication technology have shown the potentials in the research field in this context. This research work aims to design and fabricate the micro-optical components by FsLDW technology on customized substrates for specific applications. The first proposed optical application is the light sheet fluorescent microscopy using FsLDW fabricated micro-axicon which generates the Bessel beam. It is capable of generating light sheets for illumination and imaging system that can potentially be used in the intracorporal environment. The second application achieved in this work is the collimated beam tilt angle measurement using the FsLDW diffractive axicon, which produces the diffractive pattern evolution directly correlated to the tilt angle. Two types of laser direct writing systems were established and used in this research. The system Femtosecond Laser Direct Writing (FsLDW) was built with a stationary laser source and motorized sample stage, consisting of fs laser source and precision instruments, beam-guiding mirrors, a nano-positioning stage, and a real-time monitoring camera. The High-Speed Femtosecond Laser Direct Scanning system (FsLDS) with the scanning laser source and stationary sample stage was built with the laser source, beam-guiding mirrors, and Galvano scanner coupled with an f-theta lens. This system is extensively used for thin-film structure fabrication. In this study, two- and three-dimensional structures with photoresists, including SU-8, etc, as well as reduced graphene oxide (rGO), were successfully fabricated. Parametric studies were carried out to optimize the device geometry and surface quality to meet the requirements of the micro-optical elements. The micro-optics were designed to address specific applications and their optical performances were simulated using ZEMAX OpticStudio®. The physical performances of fabricated elements were compared with theoretical and simulation results and demonstrated their practical applications. In this thesis, specialized 3D and thin-film (2D) optical components were designed and fabricated, and the following applications with the optical components were demonstrated: a) The light sheet fluorescence microscopy (LSFM) with the fabricated micro-axicon created Bessel beam. The non-diffractive Bessel beam created by the micro-axicon is used for the illumination and detection of micro-objects and live cells. The proposed scheme for LSFM using this micro-axicon improves the flexibility of the system, as it replaces the bulky illumination objective and greatly improves the axial resolution of imaging compared to Gaussian beam-based imaging. It offers the possibility to reconstruct the high-quality 3D image of biological creatures non-invasively. b) Beam tilt angle measurement using the fabricated rGO thin-film diffractive axicon. The FsLDS fabricated rGO thin film diffractive axicon transforms a Gaussian beam to a Bessel beam, and hence serves as a good substitute to the commercial bulky refractive optics. The Quasi-Bessel beam generated is very sensitive to the tilt angle between the incident beam and its normal axis. As this thin-film axicon can be easily attached to any surface under consideration, it provides the flexibility to precisely detect the tilt angle between the incident beams and object surfaces.